Teachers' perceptions on formulaic language - Abdel Aziz, Shaimaa Nabil (AUC Knowledge Fountain, 2016)
Formulaic sequences (FS) are being increasingly recognized in second language learning as a key language component that has a direct impact on language proficiency. A key aspect of FS are how it can be effectively integrated within language teaching and what practices could be used to present FS and introduce it to students. Recently, researchers have reported a growing interest in using FS in teaching language in classrooms. A mixed method of data analysis was adopted in this study where both qualitative and quantitative data were collected using three instruments â€œquestionnaire, observations and interviewsâ€. 75 Arabic teachers participated in the current study, 72 of them responded to the questionnaire and the others were abstained to access the questionnaire and they were only observed in their classrooms and interviewed afterwards. The study revealed that 72 % of the participants perceive FS as important cultural language components that have direct impact on language proficiency. The participants recommended several practices and tools used to introduce FS in classrooms. Moreover, the majority of teachers acclaimed that FS should be introduced to elementary Arabic language learners. Conclusively, FS should be considered as essential cultural language components.